The Application of Restorative Justice in Handling Traffic Accident Cases by the Traffic Directorate of the North Sumatra Police - TP Banjarnahor, Jhon Fraezer; Maysarah , Andi; Hardian Silalahi, Dian (STAINI Press, 2026)
Traffic accidents are legal issues that frequently occur in society and often result in fatalities as well as material losses. The handling of traffic accident cases is generally carried out through the criminal justice system; however, this approach often fails to fully satisfy the sense of justice of the parties involved. Therefore, Restorative Justice has emerged as an alternative approach that emphasizes the restoration of relationships between offenders, victims, and the community. This study aims to examine the legal framework governing the implementation of Restorative Justice in handling traffic accident cases, its application by the Traffic Directorate of the North Sumatra Regional Police, and the efforts undertaken to overcome obstacles in its implementation. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that the application of Restorative Justice in traffic accident cases is supported by an adequate legal basis; however, in practice, it still encounters various challenges, particularly in terms of regulatory aspects, law enforcement capacity, and public understanding.